BLOCKCERTIFY: A SECURE VERIFICATION AND VALIDATION OF EDUCATIONAL CERTIFICATES USING BLOCKCHAIN TECHNOLOGY (International Journal of Food and Nutritional Sciences, 2022)
It is a rather laborious task to authenticate a document, especially in order to contact several originating agencies. Therefore, here we propose a framework that will not only secure but also simplify the verification process through blockchain. Whenever an organization like JAIN issues any document (for example, a transcript), a transaction is created in the blockchain which records metadata like the encrypted hash value of the document. To verify the document, the verifier has to know the credentials of the issuing organization like a unique wallet ID, etc. When the application receives a document for verification, it finds out the hash of the document and checks it with the database on the blockchain. If the hash code matches, then the document will be called valid; if not, tampering is established. The blockchain is so designed to remain immutable and secure that it guarantees the integrity of the transactions recorded in it and thus simplifies and improves the process of authenticity verification. The solution also includes developing an application that will make this interaction efficient.